PENGARUH STRUKTUR ORGANISASI DAN TEKNOLOGI INFORMASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN PADA PT. MANDOM INDONESIA TBK - Rosmiati, Rosmiati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
Organizational Structure is an important factor needed to influence the behavior of individuals and groups that exist within the organization. AndImplementation Information Technology has become a weapon or tool in the company's business processes that can make the flow of information runs quickly,internally and externally. Technology is expected to be a facilitator and interpreter from beginning to develop new ideas to cope with increasingly fierce competition in the future. This study aims to determine how the influence of organizational structure and information technology on the quality of management accounting information system at PT. Mandom Indonesia Tbk. Data obtained by distributing questionnaires to 35 respondents. The analytical method used is descriptive statistic, statistically processed with SEM-PLS and using SMART PLS 3.0 for windows program. Organizational structure does not affect the quality of management accounting information system. The results of this study indicate that information technology significantly influence the quality of management accounting information system.